Wind Turbine Aerodynamic Performance by Lifting Line Method - Horia Dumitrescu; Vladimir Cardos (International Journal of Rotating Machinery)
The vortex model of propellers is modified and applied to the high-speed horizontal axis turbines. The turbine blades are replaced by lifting lines and trailing vortices which shed along the blade span. The model is not a free wake model, but it is still a nonlinear one which should be solved iteratively. In addition to the regular case where the trailing vortices are constrained to distribute along a helical surface, another version, where each trailing vortex sheding from the blade grows as a free helical vortex line, is also included. Performance parameters are calculated by application of the Biot-Savart law along with the Kutta-Joukowski theorem. Predictions are, shown to compare favorably with existing numerical data from more involved free wake methods, but require less computational effort. Thereby, the present method may be a very useful tool for calculating the aerodynamic loads on horizontal-axis wind turbine blades.